The investigation of sustainable environmental performance of manufacturing companies: mediating role of organizational support and moderating role of CSR. Issue 1 (31st December 2022) - Xie, Qing; Islam, Misbah ul; Su, Ying-Yueh; Khan, Azhar; Hishan, Sanil S.; Lone, Showkat Ahmad
Abstract: China is transitioning towards green and sustainable manufacturing, considering environmental measures as per external environment demands. This research investigates the impact of green entrepreneurial orientation, social entrepreneurship, and organizational ambidexterity on sustainable environmental performance. Besides, examining the mediating role of organizational support and moderating the role of corporate social responsibilities (CSR) are also included in the aim of this research. The present study has used quantitative data of 510 respondents from China's manufacturing industry; further structural equation modelling (SEM) was employed to analyse the data. The results revealed that organizational ambidexterity, green entrepreneurial orientation, and social entrepreneurship are positively associated with sustainable environmental performance. Organizational support positively mediates among the nexus of green entrepreneurial orientation, social entrepreneurship, and sustainable environmental performance. The findings also showed that CSR significantly moderates the relationship between organizational support and sustainable environmental performance. These outcomes provide various implications for policymakers while making policies regarding CSR and sustainable environmental performance.